2012
DOI: 10.3892/mmr.2015.3502
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Scutellariae Radix inhibit low-density lipoprotein oxidation and the lipopolysaccharide-induced macrophage inflammatory response

Abstract: Traditional herbal formulas made from Scutellariae Radix (SR), the root of Scutellaria baicalensis, have previously been used in the treatment of inflammatory diseases, such as atherosclerosis. The aim of the present study was to investigate the effects of SR on low-density lipoprotein (LDL) oxidation and inflammation in macrophages, which are early events in the development of atherosclerosis. High-performance liquid chromatography photo-diode array analysis was used to obtain a three-dimensional chromatogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Recently, investigations have shown that S. baicalensis has beneficial properties such as anti-oxidative effect [16], and inhibits anti-dinitrophenyl IgE-medicated anaphylactic reactions and compound 48/80-induced histamine release and calcium uptake into rat peritoneal mast cells (RPMC) [1517]. The flavonoids such as baicalein and wogonin isolated from S. baicalensis have also various biological activities such as anti-oxidative, anti-inflammatory and anti-allergic effects [181920212223].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, investigations have shown that S. baicalensis has beneficial properties such as anti-oxidative effect [16], and inhibits anti-dinitrophenyl IgE-medicated anaphylactic reactions and compound 48/80-induced histamine release and calcium uptake into rat peritoneal mast cells (RPMC) [1517]. The flavonoids such as baicalein and wogonin isolated from S. baicalensis have also various biological activities such as anti-oxidative, anti-inflammatory and anti-allergic effects [181920212223].…”
Section: Introductionmentioning
confidence: 99%
“…The L. chinense extract has antioxidant function to scavenge the DPPH radicals, intracellular ROS, hydroxyl radicals, and superoxide (25). Scutellariae Radix was shown to reduce the ABTS and DPPH radical formation in a dose dependent manner (26). Therefore, the addition of these two medicinal herbs may have synergic effects and could help to increase antioxidant effects similar or higher than the 50 ppm and 100 ppm of BHA.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have suggested that longterm exposure to physiological or psychological stress is associated with the production of oxidative species, which cause accumulation of oxidative damage to bio-molecules (lipids, proteins, and DNA) in the brain, eventually leading to diverse neurodegenerative diseases (26). Many neurodegenerative diseases, such as Alzheimer’s and Parkinson’s diseases, are associated with excessive production of ROS and free radicals (27).…”
Section: Resultsmentioning
confidence: 99%
“…GHX02 was formed by adding Scutellariae Radix to GRHRH. GRHRH already demonstrated its anti-inflammatory effects on COPD and particulate matter induced lung injury on a mouse model 16) and previous studies reported that Scutellariae Radix inhibits the production of several inflammatory cytokines 18) and has antioxidant effects 19) .…”
Section: Introductionmentioning
confidence: 94%